2020
DOI: 10.1105/tpc.19.00844
|View full text |Cite
|
Sign up to set email alerts
|

The Tip-Localized Phosphatidylserine Established by Arabidopsis ALA3 Is Crucial for Rab GTPase-Mediated Vesicle Trafficking and Pollen Tube Growth

Abstract: PS regulates polar growth of pollen tubes One-sentence summary: Arabidopsis ALA3 plays a key role in the inverted-cone distribution of PS at the pollen tube tip, and PS is crucial for the distribution and activity of certain Rab GTPases as well as pollen tube growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 71 publications
(109 reference statements)
1
45
0
1
Order By: Relevance
“…Under normal growth conditions, seedlings grown on 1% agar MS plates for 5 days were treated with or without 4°C for the duration shown in the figure for fluorescence acquisition. Images of epidermal cells from root transition and elongation zone were acquired using a spinning disk microscope (Andor) equipped with a 63 × NA oil immersion lens, and the Z-series images were captured with the step size set at 0.5 μm (Zhou et al, 2020 ). GFP was excited with a 488-nm laser and observed using a 514-nm emission filter.…”
Section: Methodsmentioning
confidence: 99%
“…Under normal growth conditions, seedlings grown on 1% agar MS plates for 5 days were treated with or without 4°C for the duration shown in the figure for fluorescence acquisition. Images of epidermal cells from root transition and elongation zone were acquired using a spinning disk microscope (Andor) equipped with a 63 × NA oil immersion lens, and the Z-series images were captured with the step size set at 0.5 μm (Zhou et al, 2020 ). GFP was excited with a 488-nm laser and observed using a 514-nm emission filter.…”
Section: Methodsmentioning
confidence: 99%
“…Of the numerous Rabs identified in our study, members of the RabA1, D2, and E1 families were most abundant (Figure 5C; Supplemental Dataset 4). RabA proteins are most closely related to mammalian Rab11, which regulates endosomal trafficking and mediate TGN-PM trafficking in plants (Zhou, et al, 2020;Li, et al, 2017;Nielsen et al, 2008). In addition, members of the RabE family, which are orthologs of the Sec4p/Rab8 GTPase family, mediate exocytosis in yeast and mammalian cells (Rutherford and Moore, 2002) and regulate post-Golgi trafficking to the PM and to the cell plate during cytokinesis (Orr, et al, 2021;Speth et al, 2009;Ahn et al, 2013).…”
Section: Small Gtpasesmentioning
confidence: 99%
“…Phosphatidylserine (PS) is abundant in the inverted-cone zone of the apical pollen tube in Arabidopsis . Recent research has revealed that loss of apical localization of PS and significantly decreased distribution lead to obvious decreases in vesicle numbers and an obvious increase in pollen tube width, which indicates that tip-localized PS establishment is important for vesicle targeting/trafficking and polar growth of pollen tubes in Arabidopsis ( Zhou et al, 2020 ).…”
Section: Vesicle Deliverymentioning
confidence: 99%